Characterization of Humic Fertilizers from Horse, Sheep and Cattle Dung by their Density - AZIZI, PIROUZ (Asian Journal of Chemistry, 2010)
Significant differences in the humification products of horse, sheep and cattle dung can be identified by determining their density. Furthermore, the degradation rates of composts and peats can be determined with this method.